Property investment: gearing and portfolio returns. Issue 6 (15th December 2020) - French, Nick; Patrick, Michael
Abstract : Purpose: The aim of this study is to comment upon the relatively straightforward but often misunderstood role of gearing (or leverage) on the potential equity return of a property investment portfolio. Design/methodology/approach: This education briefing is an explanation of the how the addition of individual assets to a portfolio can, with gearing, impact upon the portfolio return. Findings: Although, this case study is relatively straightforward, it shows how portfolios can be geared to give enhanced returns at differing, aggregate and levels of risk. Practical implications: The process of borrowing at a bank rate below the return rate on an investment project can increase the equity return of the project as long as all incomes and discount rate remain at appropriate levels. Originality/value: This is a review of existing models.